An appraisal of the safe schools initiative and its impact on girl-child education and national development - Ibrahim, Ahmed Ladi; Ibrahim, Muhammed Sultan (Universitas Airlangga, 2025)
Education is the cornerstone of every society and a vital tool for accelerating economic, social, political and national development. However, in Nigeria, persistent attacks and kidnappings in schools pose a significant barrier to this fundamental right. In a bid to secure educational environments, the Nigerian government launched the Safe Schools Initiative in 2014. Despite this effort, school attacks and kidnappings persist, severely impacting children’s access to education in Nigeria. This study examines the Safe Schools Initiative, focusing on its impact on girl-child education and its broader implications for national development in Nigeria. Utilizing a qualitative research design, the study analyses secondary data from journals, textbooks, reports, newspapers and other internet materials through content analysis. The findings reveal that the full implementation of the Safe Schools Initiative is hindered by factors such as insecurity, inadequate funding, lack of adequate safety measures in schools, lack of awareness, and corruption and mismanagement of funds. The study concludes that investing in girl-child education is pivotal to social progress, economic stability and national development in Nigeria. The study recommends strengthening school security, providing adequate funding, ensuring transparency, and raising awareness about the initiative’s importance.